Fabrication technologies and sensing applications of graphene-based composite films: Advances and challenges - Yu, Xiaoqing; Zhang, Wensi; Zhang, Panpan; Su, Zhiqiang (Biosensors & bioelectronics, 2017)
Graphene (G)-based composite materials have been widely explored for the sensing applications ascribing to their atom-thick two-dimensional conjugated structures, high conductivity, large specific surface areas and controlled modification. With the enormous advantages of film structure, G-based composite films (GCFs), prepared by combining G with different functional nanomaterials (noble metals, metal compounds, carbon materials, polymer materials, etc.), show unique optical, mechanical, electrical, chemical, and catalytic properties. Therefore, great quantities of sensors with high sensitivity, selectivity, and stability have been created in recent years. In this review, we focus on the recent advances in the fabrication technologies of GCFs and their specific sensing applications. In addition, the relationship between the properties of GCFs and sensing performance is concentrated on. Finally, the personal perspectives and key challenges of GCFs are mentioned in the hope to shed a light on their potential future research directions. [Display omitted] •The fabrication technologies and sensing applications of GCFs were introduced.•The structure features of GCFs with special sensing performances were discussed.•The key challenges and future perspectives of GCFs were mentioned.